Interaksi Sosial dalam Pendidikan Pengasuhan Anak pada Suku Punjab - Ibnu Hajar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
The purpose of this study was to describe social interaction in the parenting pattern in the Punjab community as the manifestation of their personality. This qualitative study covered the Punjab families in the Medan city. The data were collected through participant observation and open-and-close structured questionnaire, and in-depth interview. The data were also enriched by examining the archive on Punjab's personality and parenting pattern. The data collected were analyzed by the qualitative descriptive technique. The results showed that the parenting amongst Punjab community was to shape children's personality to be responsible individuals who remained holding both traditional and religious values firmly.